2017 IEEE Conference on Control Technology and Applications (CCTA) 2017
DOI: 10.1109/ccta.2017.8062699
|View full text |Cite
|
Sign up to set email alerts
|

Laser beam pointing and stabilization by fractional-order PID control: Tuning rule and experiments

Abstract: CitationAl-Alwan A, Guo X, N'Doye I, Laleg-Kirati T-M (2017 Abstract-This paper studies the problem of high-precision positioning of laser beams by using a robust Fractional-Order Proportional-Integral-Derivative (FOPID) controller. The control problem addressed in laser beams aims to maintain the position of the laser beam on a Position Sensing Device (PSD) despite the effects of noise and active disturbances. The FOPID controller is well known for its simplicity with better tuning flexibility along with robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…The classical control tools as PID controllers [1], [7], [8] can maximize the received laser beam signal by a photodiode sensor using an actuator and stabilize the beam at the desired angle. Many studies have demonstrated that PID controllers were proved to be good control techniques for stabilizing the laser beam with minimal settling time but these classical control algorithms fail to get a good performance, specifically under vibration scenarios due to active disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…The classical control tools as PID controllers [1], [7], [8] can maximize the received laser beam signal by a photodiode sensor using an actuator and stabilize the beam at the desired angle. Many studies have demonstrated that PID controllers were proved to be good control techniques for stabilizing the laser beam with minimal settling time but these classical control algorithms fail to get a good performance, specifically under vibration scenarios due to active disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Así entonces, midiendo un pequeño porcentaje del haz, dicho espejo es capaz de estabilizar el movimiento del haz mediante la retroalimentación de la información de posición (Quanser, 2010;Landolsi et al, 2011). En los últimos años, se han diseñado y evaluado diversos enfoques de control para tales sistemas, por ejemplo, control adaptativo (Kim et al, 2004), (Pérez-Arancibia et al, 2006), método de ponderación de frecuencia (Pérez-Arancibia et al, 2009), controladores basados en PID (Landolsi et al, 2011), control PID de orden fraccionario (Al-Alwan et al, 2017), enfoques H∞ (Martinez et al, 2009), (Alizadegan et al, 2018), control resonante integral (Yue and Song, 2015); entre otros.…”
Section: Introductionunclassified
“…PID controllers with a beam-stabilized optical switch have been proposed in [2], [12] to stabilize a beam at a desired angle and maximize the optical power detected by a photodiode using a voice-coil motor actuator. Recently, a Fractional-Order PID (FOPID) controller has been implemented on a laser beam positioning system [13] and has been compared to classical PID controllers. This study has shown that the FOPID controller provides excellent stabilization properties with minimal switching time and good robustness with respect to moderate disturbances.…”
Section: Introductionmentioning
confidence: 99%